A novel heterozygous mutation in cardiac calsequestrin causes autosomal dominant catecholaminergic polymorphic ventricular tachycardia - Gray, Belinda (Heart Rhythm, 2016)
BACKGROUND: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a lethal inherited arrhythmia syndrome characterized by adrenergically stimulated ventricular tachycardia. Mutations in the cardiac ryanodine receptor gene (RYR2) cause an autosomal dominant form of CPVT, while mutations in the cardiac calsequestrin 2 gene (CASQ2) cause an autosomal recessive form. OBJECTIVE: The aim of this study was to clinically and genetically evaluate a large family with severe autosomal dominant CPVT. METHODS: Clinical evaluation of family members was performed, including detailed history, physical examination, electrocardiogram, exercise stress test, and autopsy review of decedents. We performed genome-wide linkage analysis in 12 family members and exome sequencing in 2 affected family members. In silico models of mouse and rabbit myocyte electrophysiology were used to predict potential disease mechanisms. RESULTS: Severe CPVT with dominant inheritance in 6 members was diagnosed in a large family with 2 sudden deaths, 2 resuscitated cardiac arrests, and multiple appropriate implantable cardioverter-defibrillator shocks. A comprehensive analysis of cardiac arrhythmia genes did not reveal a pathogenic variant. Exome sequencing identified a novel heterozygous missense variant in CASQ2 (Lys180Arg) affecting a highly conserved residue, which cosegregated with disease and was absent in unaffected family members. Genome-wide linkage analysis confirmed a single linkage peak at the CASQ2 locus (logarithm of odds ratio score 3.01; θ = 0). Computer simulations predicted that haploinsufficiency was unlikely to cause the severe CPVT phenotype and suggested a dominant negative mechanism. CONCLUSION: We show for the first time that a variant in CASQ2 causes autosomal dominant CPVT. Genetic testing in dominant CPVT should include screening for heterozygous CASQ2 variants.